河川底泥中六氯苯污染之環境復育研究 - 王炯強; Chiung-Chiang Wang (2006)
本研究在測試台灣與泰國底泥環境之原生菌種的脫氯能力，在台灣地區採集二仁溪及後勁溪兩條河川之底泥進行六氯苯(Hexachlorobenzene, HCB)脫氯測試，在各種培養條件下其結果均顯示遲滯期甚長(>120天)，且無法將HCB完全的降解，只有在直接添加HCB粉未的這組實驗中有較短的遲滯期(30及90天)，但仍無法將HCB完全脫氯降解，而在多氯聯苯的實驗中，經120天的培養也都沒有脫氯作用發生，另外在泰國運河的底泥中進行HCB分析，結果顯示有4個點發現HCB和1.3.5-三氯苯(1.3.5-trichlorobenzene, 1.3.5-TCB)，因為1.3.5-TCB皆由高氯數之氯苯化合物降解而來，這顯示出泰國運河底泥微生物有自行脫氯能力，因此在泰國研究中則繼續以運河底泥中的厭氧微生物來進行HCB的還原脫氯作用，實驗分兩個階段，第一階段是由10點取得底泥微生物並應用於脫氯實驗上，過程中使用底泥加河水之底泥水再添加5g/L的yeast extract (YE)或是不添加。所有點中之HCB在14天後開始脫氯， 28-42天完全脫氯，未添加YE部份則在14至28天後有較緩慢的脫氯活動。事先添加養份和厭氧處理之組別在7天後，運河底泥微生物即有HCB之脫氯能力，並在6星期內完全脫氯，第二階段為評估HCB在經前處理及未處理的新鮮底泥水中之脫氯作用，結果顯示，底泥與水比例越高的組別其脫氯能力越強，底泥水不論過濾與否，都有HCB脫氯作用發生，另外，底泥水經前厭氧處理的時間越長，則對HCB的脫氯能力越佳。本研究結果顯示HCB脫氯菌廣闊的分佈在泰國運河沿岸的底泥，而且也顯示HCB污染的運河底泥之中有環境復育的可行性。 In order to investigate the hexachlorobenzene (HCB) dechlorintion ability of indigenous microbes in Taiwan and Thailand, river and canal sediments were collected and introduced in the HCB dechlorination tests. Most sets by using anaerobic microbes from Er-Jen River and Ho-Tsin River slowly dechlorinated HCB with a longer lag phase more than 120 days, and only those sets that added powder-like HCB showed short lag phase. Futhermore, these microbes cannot dechlorinate polychlorinated biphenyls within 120 days of incubation. In contrast to the weak HCB dechlorination ability of Taiwan river sediment anaerobes, indigenous microbes from Thai canal sediments showed more active dechlorination. The reason for Thai canal bacteria possessing novel HCB dechlorination potential might because the Canal was found contaminated by HCB. The HCB dechlorination experiments by Thai Canal microbes included two stages. In the first stage, sediments from 10 different sites were collected and the HCB dechlorination ability of the sediment microbes was also tested. In the sets with yeast extracts (YE), all 10 sites of microbes showed dechlorination activity after 14 days of incubation and completed the dechlorination within 28 ~ 42 days. In the sets without YE, the lag phase was about 14 ~ 28 days. In the second stage, HCB ...